Developing management practices to support joined-up governance - Carey, Gemma; Harris, Patrick (2016)
Various forms of boundary-crossing practices continue to proliferate in public management and public service provision (i.e. activities that require engagement and collaboration across sectors, institutions, and organisations). Yet the dynamic nature of this type of joined-up working is proving to be a major management challenge. In this paper, we bring a number of concepts to bear on the management of joined-up and cross-boundary working in public management of complex social issues. Firstly, we present the concept of adaptive management, which we draw from field of environmental policy and planning (and human ecology). Secondly, we introduce a rethinking of the role of policy targets using a complexity lens. These concepts are integrated into a practice heuristic (or framework) designed to assist cross-boundary policy implementation in real-world settings. We argue that adaptive management approaches may have significant utility for ensuring effective governance in uncertain environments. - Reproduced. 11
Keywords: Public administration; Development administration